Genetic diversity of Rhizobium spp. isolated from soil samples of Bangladesh - Tanim, Md Tauhidul Islam; Chowdhury, Md Miraj Kobad; Bari, Latiful; Rahaman, Md Mizanur; Rahman, Sabita Rezwana; Rahman, Md Majibur (Bangladesh Journal of Microbiology, 2019)
Rhizobia are Gram-negative soil-inhabiting bacteria commonly found in nodules of leguminous plants. These bacteria exclusively fix atmospheric nitrogen into ammonia, which is convertible to urea to serve natural fertilizer to the plants. However, rhizobial microbiota of Bangladesh have been studied poorly. Here, twenty isolates were identified as Rhizobium through observation of cultural characteristics, morphological characteristics and different biochemical tests. Isolates differed from one another in terms of their stress response characteristics like salt-stress tolerance,temperature tolerance, antibiotic susceptibility, and pH. Most of the isolates were resistant to ampicillin and erythromycin and streptomycin; and were sensitive to kanamycin and ciprofloxacin. Isolates were clustered into three genotypic groups according to the banding patterns of Amplified Ribosomal DNA Restriction Analysis (ARDRA). All the strains in ARDRA group 1 were Rhizobium azibense, and the others were Rhizobium bangladeshense and Rhizobium qilianshanense. Future studies would validate their capacity of nitrogen fixation and the scope of improvement of these strains to increase their efficiency of nitrogen fixation. Bangladesh J Microbiol, Volume 36 Number 1 June 2019, pp 07-10